Enhancing Online Teaching Methods Through Leadership Innovations - Sharma Manjari; Gupta Sharad (Scientific Bulletin)
This paper explores the crucial role of leadership in enhancing online teaching methods through innovative approaches. As online education becomes increasingly important, particularly following the COVID-19 pandemic, effective leadership is vital for addressing both the potential and challenges of digital learning environments. This study emphasizes the integration of advanced technologies such as AI and adaptive learning systems and the importance of inclusive educational strategies. The research also highlights leadership models that foster strategic planning, technological innovation, and inclusivity to improve online education outcomes. Practical recommendations for fostering student engagement, maintaining academic integrity, and addressing the digital divide are discussed. These findings provide a framework for educational leaders to successfully navigate the complexities of online education and to implement technologies that enhance learning experiences for diverse student populations.